2014
DOI: 10.1007/s00348-014-1849-7
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: a new insight into the tip leakage vortex using stereo-PIV

Abstract: of a specific tip clearance for which the vortex strength is maximum and most prone to generating cavitation. List of symbols c Hydrofoil chord h Maximum foil thickness W ∞ Inlet velocity p ∞ Inlet pressure x, y, z Cartesian coordinates u, v, w Spanwise, transverse and axial velocity x c , y c Vortex center coordinates r c Vortex core radius Re c Reynolds number (W ∞ c/ν) α Incidence angle τ Normalized tip clearance (gap/h) ω Vorticity Γ Circulation Γ * Normalized circulation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(71 citation statements)
references
References 31 publications
3
68
0
Order By: Relevance
“…SPIV measurements of Chang et al (2011) and Dreyer et al (2014), similar to the present study, both focused on the effect of the velocity field on vortex cavitation, but no velocities were measured in the presence of cavitation.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…SPIV measurements of Chang et al (2011) and Dreyer et al (2014), similar to the present study, both focused on the effect of the velocity field on vortex cavitation, but no velocities were measured in the presence of cavitation.…”
Section: Introductionmentioning
confidence: 73%
“…The global vortex detection method by Graftieaux et al (2001) and used in Dreyer et al (2014) was also considered. This method is much more robust due to lower susceptibility to noise in the instantaneous vector fields.…”
Section: Page 4 Of 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Lei Shi, Zhang, Zhao, Weidong Shi and van Esch, Journal of Fluid Science and Technology, Vol.12, No.1 (2017) 7 low pressure in the vortex core (Arndt, 2002;Higashi et al, 2002;Murayama, 2006). Thus, cavitation inception is often coupled with vortex structures, such as tip leakage, trailing and hub vortices as well as turbulent vortex structures developing in regions of flow separation.In the aforementioned research, much attention has been paid to the tip leakage vortex cavitation around the fully-wetted hydrofoils (Boulon et al, 1999;Park et al, 2006;Dreyer et al, 2014). Although many progress has been made in regard to the vortex structures and self-induced cavitation, some important parameters are still missing in actual hydraulic machines, for instance, the body force in rotating frame which can alter the cavitation phenomenon.…”
mentioning
confidence: 99%
“…Moreover, numerous studies have shown that the re-entrant jet is considered as the main mechanism responsible for the shedding of cavity (Arndt et al 2000, Altimira and Fuchs, 2015, Dreyer et al 2014, Decaix and Goncalvès, 2013, Goncalvès and Charrière, 2014, Roohi et al 2013, Zhang et al 2014and Yu et al 2014.…”
Section: Introductionmentioning
confidence: 99%